Pengaruh Sumberdaya Manusia dan Motivasi Belajar terhadap Peningkatan Keterampilan Manajemen Usaha Makanan dan Minuman - Eka Rachmawati; Titik Sulistyani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to 1) determine the motivation of students to learn in the food and beverage business management course, 2) determine the improvement of students' skills in the food and beverage business management course. The research method used in this study is classroom action research with a project based learning approach model through 2 cycles. The sample in this study was 38 students with a sampling technique using the purposive sample method. The data collection technique was by using questionnaires and observations. The data analysis used was descriptive, namely by describing the results of the questionnaire diagram. The results of the study obtained were in the high category according to the benchmark assessment (PAP). It can be described as follows, namely in critical thinking there was an increase of 40% from 50% to 90%, in creativity from 55% to 93% for a sharp increase in communication from 40% to 89%, collaboration from 40% to 83%, connection from 45% to 80%. Students' learning motivation in carrying out learning cannot be separated from the desire and desire to succeed and the appreciation in learning given by lecturers in the form of good grades and appreciation. Motivation will cause a person to want to know, act, understand, believe, or acquire certain knowledge, skills, attitudes, or values.